The Application of Selected Inventive Methods in the Development of Guidelines for Modernisation Concept of the Bus Station in Polanica-Zdrój (Poland) - a Case Study - Bocheńska-Skałecka, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper outlines the outcomes of the deployment of selected heuristic methods in the initial stages of the design process for a modernised public space. The process was carried out in accordance with the objective of adapting the space to contemporary user needs and environmental conditions. The research is situated within the broader context of exploring solutions for shaping public spaces inspired by nature, with the aim of contributing to the enhancement of both the psychophysical condition of humans and the state of the environment.
Keywords: public space; sustainable development; TRIZ; "brainstorming"